Morphological characteristics of Phalaenopsis hybrids treated with 1500 ppm colchicine - Samanhudi Samanhudi; Sri Hartati; Ida Rumia Manurung; Ayu Lestari (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
The increasing number of Phalaenopsis sp. enthusiasts needs to be balanced with the availability of good-quality cultivars, one of which can be achieved by improving flower morphological characteristics through colchicine induction. Colchicine-induced plants often exhibit superior traits such as larger, thicker, and more durable flowers. This study aimed to investigate the effect of a 1500 ppm colchicine concentration on the floral morphological characteristics of the Phalaenopsis sp., with a particular focus on flower size, petal thickness, and sepal morphology. This research provides genetic diversity information on Phalaenopsis sp., which can serve as a basis for future breeding programs and as a reference material for orchid growers and researchers. The materials used were flower buds of three Phalaenopsis varieties: Phalaenopsis Fuller’s Sunset, Phalaenopsis Golden Tree, and Phalaenopsis OX X-Ray. Each treatment was replicated three times. Morphological data were analyzed qualitatively through scoring and converted into binary data according to the Guide Book of Orchid Plant Characterization by the Ornamental Plant Research Center (2007). The results showed that 1500 ppm colchicine affects Phalaenopsis Fullers Sunset in the form of rhombus-shaped petals, and on Phalaenopsis Golden Tree in the form of pointed lateral sepal tips, concave transverse and longitudinal cross-sections of petals, and on Phalaenopsis OX X-Ray in the form of split dorsal sepal edges, and open petal arrangement. Overall, colchicine treatment also induced apparent enlargement of flowers in all three Phalaenopsis hybrids. Keywords: chromosome; flower morphology; mutagenesis; ornamental plant; polyploidy